2011
DOI: 10.1111/j.1751-553x.2011.01369.x
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma protein oxidation is correlated positively with plasma iron levels and negatively with hemolysate zinc levels in sickle‐cell anemia patients

Abstract: Alterations of proteins, lipids, and ions in the plasma and erythrocyte of steady-state patients with SCA were demonstrated. Some of these alterations are related with each other and with the oxidative stress observed in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…SCD patients display moderate hypocholesterolemia, with reduced high-density lipoprotein cholesterol and apolipoprotein A-I. 44,45 Our present work thus suggests that RBC MPs carry heme in SCD plasma. Other types of tissue injury, such as bacterial infections or ischemia, might also stimulate erythrocytes, promote vesiculation and shift heme compartmentalization toward MPs.…”
Section: Heme-laden Mps and Mouse Kidney Vasoocclusionssupporting
confidence: 55%
“…SCD patients display moderate hypocholesterolemia, with reduced high-density lipoprotein cholesterol and apolipoprotein A-I. 44,45 Our present work thus suggests that RBC MPs carry heme in SCD plasma. Other types of tissue injury, such as bacterial infections or ischemia, might also stimulate erythrocytes, promote vesiculation and shift heme compartmentalization toward MPs.…”
Section: Heme-laden Mps and Mouse Kidney Vasoocclusionssupporting
confidence: 55%
“…This indicates that despite similar dietary intake, SCD has an effect on lipid metabolism. These results are consistent with previous reports that cholesterol and LDL levels are lower in SCD patients (Oztas et al , 2012). The effect of SCD on lipid metabolism may be due to increased erythropoietic activity or a consequence of the haemolytic anaemia in SCD (Zorca et al , 2010; Oztas et al , 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Besides the manifestations of chronic hemolysis, vaso-occlusion, endothelial injury and inflammation [1], SCA is also a disease of increased oxidative stress [2]. Previous studies have reported increased levels of malondialdehyde [2] and protein carbonyl [3] in the plasma of SCA patients.…”
Section: Tablementioning
confidence: 99%
“…Therefore, more modifications (such as the change in the number of disulfide linkages, more folding or unfolding, change in the amount of malondialdehyde adducts and methemalbumin formation) are expected in the albumin fraction in this group. We previously reported increased protein oxidation by carbonyl modification in SCA patients [3]. Another study reported albumin oxidation in the form of malondialdehyde adducts in SCA patients [17].…”
Section: Tablementioning
confidence: 99%